ANALISIS PERTANGUNGJAWABAN TINDAK PIDANA PENCUCIAN UANG YANG DILAKUKAN OLEH KORPORASI - Tamyiz, Qiaro; Taun, (The Juris, 2023)
The concept of criminal liability against corporations s a new concept criminal law. The difficulty of mposing responsibility on the corporation n committing the crime of laundering creates problems, namely when the corporation s deemed to have committed a crime of money laundering and how s the responsibility mposed. To find out this, the researcher used the juridical-normative method, with secondary data sources through a statutory approach, a legal analytical approach and a case approach and a qualitative data analysis method. The results of the study show that Law No. 8 of 2010 PPTPUU does not directly regulate when a corporation commits the crime of money laundering, so the author needs to nterpret and link the articles of money laundering with corporations as the subject of a crime. The actor acts as the directing mind by mposing on the corporation and / or corporate controlling personnel. There s no explanation for the mposition of corporate responsibility so that n order to transfer the burden of responsibility to the corporation and / or corporate control personnel, t s necessary to use the doctrine of vacarious liability theory with the theory of responsibility approach: Delegation (doctrine of delegation), dentification (doctrine of dentification) and Aggregation (doctrine of aggregation), so that corporations can be punished / held accountable.